Fenomenologi Transendental Tentang Transformasi Makna Uang Tunai Pada Konsumen Pusat Perbelanjaan Modern Kota Pekanbaru Di Era Adopsi QRIS - Rahmawati Rahmawati (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital payment systems through the Quick Response Code Indonesian Standard (QRIS) has driven changes in people's transaction patterns towards a cashless society. However, the use of cash has not been completely abandoned because it still has an inherent subjective meaning in everyday life. This study aims to analyze the transformation of the meaning of cash amidst the increasing adoption of QRIS among consumers of modern shopping centers in Pekanbaru City. The study used a qualitative approach with Edmund Husserl's transcendental phenomenology method to understand the participants' lived experiences and awareness regarding the use of cash and digital payments. Data were obtained through in-depth interviews with 15 participants from Generation Z, Millennials, and Generation X, and supported by participant observation. Data analysis was carried out through stages of phenomenological reduction, meaning grouping, and thematic analysis. The results of the study identified three main themes: cash as a means of budget control, cultural heritage and symbols of locality, and the experience of loss of presence due to the digitalization of transactions. These findings indicate that cash still has important psychological, social, and cultural values. The novelty of the study lies in revealing the subjective experiences of Pekanbaru residents regarding the meaning of cash in the era of QRIS-based digital payment transformation.